A shallow gas flat spot anomaly in the Bjørnøyrenna Fault Complex in the Barents Sea: processing and interpretation of P-Cable 3D seismic data - Lium-Wickler, Adrian (UiT Norges arktiske universitet, 2015)
This thesis analyzed P-Cable high-resolution 3D seismic data from the Bear Island Fault Complex in the southwestern Barents Sea acquired during a Helmer Hanssen cruise in 2012. Hence, the thesis is divided into two parts: the first part of the thesis focuses on the steps taken during the processing of the raw seismic data from the Lundin 2012 Area-A survey located at the Bear Island Trough Fault Complex. The processing includes assigning geometry to the seismic data, correcting the source-receiver offset, and then assembling a cube from the seismic lines through CDP Binning. After creating the 3D cube, the signal to noise ratio is improved through filtering procedures. For this project, the Ormsby filtering was used to remove noise from the seismic signal. Ghost signals were removed trough a DeGhosting process. Import of tidal data was done to attenuate some of the noise created by variations in water depth. Normal move out and stacking was done before migrating the data. After migration, the data was exported to Petrel for the interpretations. The second part of the thesis focuses on the interpretation of the processed 3D seismic data with emphasis on hydrocarbon indicators, shallow gas accumulations, and potential migration pathways. The stratigraphy of the area was correlated through well 7219/9-1. This was done by tracing stratigraphical boundaries across several 2D lines before connecting with the dataset. Within the dataset, I observe the Top Hekkingen Formation up to the Torsk Formation. The top of the Torsk Formation is cut by the Upper Regional Unconformity (URU), which is overlain by glacigenic sediments. Large-scale normal faults interpreted as half-gradens, with small-scale faults within the blocks, are seen in the eastern part of the dataset. On the seabed, we see features such as iceberg ploughmarks and pockmarks. Pockmarks mainly occur within the ploughmarks and are located above flat spots seen at the URU in seismic cross section. Most of the gas accumulations are observed at the URU with the ...